Prestasi Akademik Siswa Sekolah Menengah Pertama (SMP) Ditinjau Dari Konsep Diri Akademik Dan Kecerdasan Emosi - Anwar Fuadi (UIN Antasari Banjarmasin, 2020)
ABSTRACT This study aims to determine the correlation between junior high school (SMP) student academic achievement in terms of academic self-concept and emotional intelligence. The hypothesis of this study is that there is a positive correlation between academic self-concept and emotional intelligence with the academic achievement of junior high school students. Subjects in this study amounted to 193 class students, data collection was carried out using two scales, the academic self-concept scale and emotional intelligence scale and for academic achievement in the form of documentation of students' final semester scores. Data analysis using multiple regression analysis techniques. The results showed that there is: a very significant relationship between academic self-concept and emotional intelligence with academic achievement.